The impact of Land use Change on Water Pollution Index of Kali Madiun Sub-watershed - Susanti, Pranatasari Dyah; Miardini, Arina (Forum Geografi, 2017)
Land use change is one of the effects of population growth and increased human activities. Land use change that overlooked the rule of ecosystem sustainability has a propensity to adversely affect the environment, including the decline of water quality. Kali Madiun is a sub-watershed of Bengawan Solo Watershed that allegedly endured the impacts of land use change. This study aimed to investigate the impacts of land use change on the water quality index of Kali Madiun Sub-watershed. Land use change analysis was done by overlay analysis of spatial data including the maps of land use in 2010 and 2015. Samples were the surface water in the upper, middle and lower part of Kali Madiun Sub-Watershed. Water quality analysis was carried out by comparing the results of water quality parameter assessment based on Government Regulation No. 82 of 2001, while water quality index was figured out by an assessment based on the Decree of the Minister of Environment No. 115 of 2003. The results indicated that during the five years observation, there were land use changes in the upper, middle and lower part of Kali Madiun Sub-watershed. Several parameters increased in 2010 to 2015, namely: TDS, BOD, COD, nitrate, detergents, oils and greases. Pollution index shifted from slightly polluted in 2010 into moderately polluted in 2015. We propose a strategy to solve these problems by the involvement of stakeholders and the participation of local community in managing both domestic and industrial wastes. Also, it should be supported by palpable regulations related to land conversion. Furthermore, it is expected that the effort will reduce the potential of pollution and improve the water quality.